Knowledge, attitude, and practice toward road safety regulations among college students in Telangana state - Jothula, Kishore Yadav (J Educ Health Promot, 2021)
BACKGROUND: Road traffic continues to be a major developmental issue and a public health concern. Road accidents in India kill almost 1.5 lakh people annually, and India accounts for almost 11% of the accident-related deaths in the world. Prevention of road traffic accidents is very crucial by creating awareness and taking proper measures toward road safety. AIMS: The aims of this study were to assess the knowledge about road safety regulations and to assess the attitude and practices regarding road safety regulations. SETTINGS AND DESIGN: This cross-sectional study was conducted in a pharmacy college. SUBJECTS AND METHODS: Study participants were all 4 academic years' pharmacy students who know driving two- or four-wheeler motor vehicle. Data were collected from a sample of 132 by predesigned pretested semi-structured questionnaire. STATISTICAL ANALYSIS USED: Data were presented in proportions with confidence interval using SPSS ver. 22. RESULTS: 81.1% of the participants knew the minimum age to obtain driving license. Only 16% follow the road signs strictly and 76% wear helmet for long-distance ride. Poor attitude was observed for wearing helmet for short-distance ride, pillion rider wearing helmet, and drink and drive. CONCLUSIONS: Majority of the participants were aware of road safety regulations. In spite of having positive attitude toward road safety measures by participants, they could not translate attitude into practice.